The Joseph Winterbotham Collection : A Living Tradition. - Wood, James N.; DelliQuadri, Lyn; The Art Institute of Chicago (Chicago : The Art Institute of Chicago, 1986)
Matisse, Henri ; Clarenbach, Max ; Junghanns, Julius Paul ; Forain, Jean Louis ; Gauguin, Paul ; Putz, Leo ; Besnard, Albert ; de Toulouse-Lautrec, Henri ; Friesz, Emile Othon ; Marchand, Jean Hippolyte ; Braque, Georges ; etc.
The Joseph Winterbotham Collection have been transferred to the Art Institute's general collection and remain in the museum as gifts of the Joseph Winterbotham Collection.
boek